Trace of the effect of social innovation in patent data - D. P. Fedulkin; O. V. Cherchenko (Ekonomika Nauki)
It is proposed to consider as a subtype of social innovation a significant change in the interaction of the scientific team that has arisen as a result of a scientific or scientific-technical project, generating specific conditions for obtaining and (or) developing new knowledge and, possibly, the economic benefits of such a change. A hypothesis has been put forward that the use of patent data characterizing individual results of scientific and technical activity allows us to identify scientific or scientific and technical projects and their results, which have become drivers of the growth of social innovations or social effects of innovation, which consist in expanding the boundaries of the previous scientific school of performers or creating new scientific school, or in expanding the boundaries of research. The hypothesis was tested on a number of completed projects of the federal target program «Research and Development in Priority Directions for the Development of the Scientific and Technological Complex of Russia for 2014–2020».